PENGARUH CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP LOYALITAS MEREK - Bayu Andika Dipura (Manajemen Bisnis, 2016)
This research aims to examine effects of brand image and perceived quality simultaneously and partially on brand loyalty Indosat card users. Methods of data collection using questionnaires. The sample size consisted of 125 respondents taken by accidental sampling. Data were analyzed using a range of scales and ordinary least squares (OLS). The results show the brand image and perceived quality have influence simultaneously and partially on brand loyalty with the determination coefficient is 71,9%. This means that if the brand image and perceived quality, brand loyalty is high then high, and vice versa. Variable brand image dominant influence on brand loyalty Indosat card users.